Konsep Bangsa Ideal Perspektif Al-Qur’an dan Tanakh: Studi Analisis Komparatif QS Ali ‘Imran/3: 110 dan Tanakh - Muhammad Syawal Rosyid Darman (AL-AQWAM: Jurnal Studi Al-Quran dan Tafsir, 2022)
This paper discusses the concept of an ideal nation from a biblical perspective. The object of study in this paper is the Koran and the Tanakh. The author compares the two holy books and then analyzes the concept of an ideal nation from Plato's perspective. The result of this paper is that there are two mappings of the concept of an ideal nation, the first concept is the status of an ideal nation judged by its determination to keep His covenant between him and God. The second concept is that to be ideal, a nation must apply several elements, these elements according to the Qur'an are amar ma’ruf nahi munkar. The philosopher Plato has an idea similar to the Koran, according to him a nation must be based on justice. This second concept opens the possibility that all nations have the potential to become ideal nations.